1996
DOI: 10.1172/jci118937
|View full text |Cite
|
Sign up to set email alerts
|

Kidney, splanchnic, and leg protein turnover in humans. Insight from leucine and phenylalanine kinetics.

Abstract: The rate of kidney protein turnover in humans is not known. To this aim, we have measured kidney protein synthesis and degradation in postabsorptive humans using the arterio-venous catheterization technique combined with 14 C-leucine, 15 N-leucine, and 3 H-phenylalanine tracer infusions. These measurements were compared with those obtained across the splanchnic bed, the legs ( Ϸ muscle) and in the whole body. In the kidneys, protein balance was negative, as the rate of leucine release from protein degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 57 publications
6
62
2
1
Order By: Relevance
“…In addition, our data demonstrated that the kidney participates in leucine transamination; in all three groups studied reamination and deamination rates consistently ranged from 6 to 12 μmol/min, corresponding to between 10 and 20% of whole-body transamination under conditions of wellcontrolled insulin. These findings are in contrast to the previous study [13], which reported renal transamination rates below zero. The discrepancy could relate to the different patient categories studied, because it cannot be excluded that patients with hypertension and cardiac disease may have subtly compromised renal function.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, our data demonstrated that the kidney participates in leucine transamination; in all three groups studied reamination and deamination rates consistently ranged from 6 to 12 μmol/min, corresponding to between 10 and 20% of whole-body transamination under conditions of wellcontrolled insulin. These findings are in contrast to the previous study [13], which reported renal transamination rates below zero. The discrepancy could relate to the different patient categories studied, because it cannot be excluded that patients with hypertension and cardiac disease may have subtly compromised renal function.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding that 5-10% of wholebody phenylalanine and leucine fluxes occur across the renal bed is in line with a previous study [13], which reported a renal component of 10% in patients with hypertension and cardiac disease. In addition, our data demonstrated that the kidney participates in leucine transamination; in all three groups studied reamination and deamination rates consistently ranged from 6 to 12 μmol/min, corresponding to between 10 and 20% of whole-body transamination under conditions of wellcontrolled insulin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We previously evaluated protein turnover across the human kidney in studies on the basis of the organ mass balance associated with leucine isotope kinetics (14,15). Kidney protein turnover, as compared with muscle and splanchnic turnover, is characterized by the highest rates of protein synthesis and amino acid oxidation.…”
mentioning
confidence: 99%